Instrumen Kemampuan Creative Problem Solving Siswa SMA pada Materi Energi Alternatif: Analisis Model Rasch - Icha Nurrohmah; Lina Aviyanti; Ida Kaniawati (Mataram University, 2026)
This study aims to evaluate the quality of an assessment instrument measuring students’ Creative Problem Solving (CPS) skills in the context of alternative energy using the Rasch Model. CPS is a crucial competency in 21st-century physics learning; however, students’ CPS abilities are often found to be relatively low, partly due to the limited availability of valid and reliable assessment instruments. This research employed a descriptive quantitative design involving 35 eleventh-grade students from a private senior high school in Bandung. The instrument consisted of 18 open-ended items analyzed using Ministep software based on the Rasch Model. The results indicated that the instrument satisfied the unidimensionality assumption, with a raw variance explained value of 51.2% and an unexplained variance in the first contrast of 8.9%, indicating that the instrument consistently measures a single CPS construct. All items demons trated good model fit and high reliability, as reflected by a person reliability of 0.84, item reliability of 0.81, and Cronbach’s Alpha of 0.93, suggesting that the instrument produces stable and reliable measurements. Furthermore, the distribution of item difficulty ranged from very easy to highly difficult, indicating that the instrument can effectively differentiate students’ abilities across various proficiency levels. These findings confirm that the instrument is valid, reliable, and capable of providing more objective measurements of students’ CPS skills. This study contributes to addressing the limitations of CPS assessment tools by providing a systematically validated instrument based on the Rasch Model, particularly in the context of alternative energy learning.